Self-perception and Parents’ Perceptions of the Nutritional Status Based on BMI in School Children of Dhaka City (TAJ: Journal of Teachers Association, 2020)
Background & objective: Childhood underweight or overweight prevention efforts are unlikely to be successful without a better understanding of how parents perceive the problem of underweight or overweight in their children. This study was carried out with the objective of comparing perceptions (parents’ and self) of the nutritional status with the actual nutritional status measured by BMI.Materials & Methods: This Cross-sectional study was carried out in the Department of Pediatrics, Sir Salimullah Medical College, Mitford hospital, Dhaka over a period of 12 months, from July 2008 to June 2009. Three schools in Dhaka Metropolitan city were selected by multistage sampling (lottery method). A self– administered parents’ questionnaire was filled by parents. Then the student’s nutritional status was defined according to age and gender specific body mass index percentile from CDC-2000 reference as underweight (< 5th percentile), normal (5th - 85th percentile), overweight (85th -